Nanoscale infrared (IR) spectroscopy and imaging of structural lipids in human stratum corneum using an atomic force microscope to directly detect absorbed light from a tunable IR laser source. Issue 6 (8th May 2013) - Marcott, Curtis; Lo, Michael; Kjoller, Kevin; Domanov, Yegor; Balooch, Guive; Luengo, Gustavo S.
Abstract An atomic force microscope (AFM) and a tunable infrared (IR) laser source have been combined in a single instrument (AFM‐IR) capable of producing ~200‐nm spatial resolution IR spectra and absorption images. This new capability enables IR spectroscopic characterization of human stratum corneum at unprecendented levels. Samples of normal and delipidized stratum corneum were embedded, cross‐sectioned and mounted on ZnSe prisms. A pulsed tunable IR laser source produces thermomechanical expansion upon absorption, which is detected through excitation of contact resonance modes in the AFM cantilever. In addition to reducing the total lipid content, the delipidization process damages the stratum corneum morphological structure. The delipidized stratum corneum shows substantially less long‐chain CH2‐stretching IR absorption band intensity than normal skin. AFM‐IR images that compare absorbances at 2930/cm (lipid) and 3290/cm (keratin) suggest that regions of higher lipid concentration are located at the perimeter of corneocytes in the normal stratum corneum.